Non verbal communication: a contribution to breastfeeding counseling - Leite, Adriana Moraes (2004)
The "Course on Breastfeeding Counseling", elaborated and implemented by the United Nation's Children's Emergency Fund - UNICEF in partnership with the World Health Organization - WHO, represents one of the most important initiatives towards the valorization of women as breastfeeding agents. With a view to understanding and facilitating the application of the nonverbal communication skills this course intends to develop among professionals, this study aims to organize the theoretical frameworks that will support the teaching of Listening and Learning Skills -1 - "Use of non verbal communication", considering the concepts of human communication found in different authors. We found out that the skills of the course are centered in techniques only directed at the professional's attitudes. However, it is necessary to pay attention to women's nonverbal signs, as they reflect their emotions. These signs can indicate the difficulties women are facing, their interpretations regarding the interaction elements in their context and, often, they are indicative of how they will direct the breastfeeding process.